Analysis of Lecturers' Speech Actions in Learning Interaction and Its Implications for Student Interest in Arabic Literature Students of UMI - Nurtaqwa Amin (Tamaddun Life, 2018)
This study discusses the use of speech acts by lecturers and students in the learning process and their implications for increasing student interest in learning Arabic at the Muslim University of Indonesia. The method used is a qualitative analysis method with a speech act analysis approach. Lecturer and student communication events are an important indicator in the learning process because they have an impact on the level of student interest in learning towards the learning material presented in the lecture. The purpose of this study was to analyze the types of speech acts used by lecturers on students and to analyze the impact of their influence on the level of student interest in learning in the learning process at the Arabic Literature Department. This research is expected to theoretically be able to contribute to the development of pragmatics, especially speech acts. and practically this research is expected to make a positive contribution to the development of the alma mater and language character education which creates positive duplication in speech and contains ethical and proportional cultural values. The results show that seen from the way of delivery, the speech acts used are more direct, which is called the meaning of locus than the way of delivery that is indirect (indirect) or is called the meaning of illocution. However, in perlocution, the lecturers' speech acts towards students received a positive response or attitude from most students (ranging from 60-65 percent). It can be argued that although most of the direct speech acts are used, they can be colored by the use of utterances according to the guidance of the quranic speech act patterns, so that the acts.